Climate Change and Resilience of Terrestrial Ecosystems: Case of the Androy Region, Madagascar - Firengea U. L. Gabriel; Rejo Fienena (Ite Ngabdi, 2026)
This study examined the impacts of climate change on the resilience of terrestrial ecosystems in the Androy Region, southern Madagascar. A mixed-methods research design was employed, integrating climatic data analysis, household surveys, key informant interviews, field observations, and document review to assess ecosystem responses and community adaptation strategies. The findings revealed that declining rainfall, rising temperatures, and recurrent droughts have accelerated land degradation, reduced vegetation cover, intensified food insecurity, and weakened ecosystem resilience. The study also identified socioeconomic and institutional constraints, including limited agricultural resources, inadequate infrastructure, and gender inequality, as factors reducing adaptive capacity. Nevertheless, ecosystem restoration, sustainable land management, and community-based natural resource management emerged as important resilience strategies. The study concludes that integrated ecosystem restoration, climate adaptation, and strengthened institutional support are essential for enhancing ecosystem resilience and promoting sustainable development in the Androy Region.